2023
DOI: 10.3389/fchem.2023.1190630
|View full text |Cite
|
Sign up to set email alerts
|

Improving osteoinduction and osteogenesis of Ti6Al4V alloy porous scaffold by regulating the pore structure

Abstract: Titanium alloy scaffolds with a porous structure have attracted much attention in bone defect repair. However, which pore structure is more beneficial to bone defect repair is controversial. In the present research, the Ti6Al4V alloy porous scaffolds with gradient pore sizes were designed and fabricated. The microstructure characterization, tests of mechanical properties, and in vitro and in vivo experiments have been performed to systematically evaluate the effect of pore size on osteoinduction and osteogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…This contributes to a phenomena known as "stress shielding" whereby there is a reduction in bone density as a result of removal of the typical stress from the bone by an implant. The stress-shielding effect can create poor bone integration with scaffolds and eventually can lead to aseptic loosening [112]. The ideal implant has the lightweight properties of titanium alloy and a similar elastic modulus as bone without sacrificing mechanical strength.…”
Section: Improving Osseointegration Through Engineering and Implant D...mentioning
confidence: 99%
“…This contributes to a phenomena known as "stress shielding" whereby there is a reduction in bone density as a result of removal of the typical stress from the bone by an implant. The stress-shielding effect can create poor bone integration with scaffolds and eventually can lead to aseptic loosening [112]. The ideal implant has the lightweight properties of titanium alloy and a similar elastic modulus as bone without sacrificing mechanical strength.…”
Section: Improving Osseointegration Through Engineering and Implant D...mentioning
confidence: 99%
“…Finally, by implanting the implant into rabbits, it was concluded that the biological performance of the P700 group with an actual pore diameter of approximately 600 µm was better than that of the other two groups. Wang et al [77] created consistently sized cubic pores measuring 300 µm, 400 µm, 500 µm, 600 µm, 700 µm, 800 µm, 900 µm, and 1000 µm through a combination of in vivo and in vitro experiments. The structural modifications and experimental outcomes are depicted in Figure 4d-f.…”
Section: Pore Sizementioning
confidence: 99%
“…Cells are stained with actin filaments (red) and nuclei (blue) [76]. (D): Pore size analysis of Ti6Al4V and cell-staining results(live: green; dead: red), the green circle represents the pore size measured by Image-J software (Version 1.54) [77]. (E): Optical pictures of porous titanium alloys with different pore sizes [77].…”
Section: Pore Sizementioning
confidence: 99%
See 2 more Smart Citations